Truncated Star Formation and Ram Pressure Stripping in the Coma Cluster - Ariel O. Broderick; Ian D. Roberts; Michael J. Hudson (The Astrophysical Journal)
We use 45 galaxies from the Mapping Nearby Galaxies at Apache Point Observatory survey to study the physical drivers of star formation quenching in the Coma Cluster. We measure specific star formation rate (sSFR) radial profiles for the Coma sample as well as a control sample of noncluster field galaxies. We find that compared to the control sample, galaxies within the Coma Cluster have sSFR profiles that fall off more steeply with galactocentric radius. We then apply a toy model based on slow-then-rapid quenching via ram pressure stripping. We find that this model is able to reproduce the difference in sSFR profiles between field and Coma galaxies. These results demonstrate that ram pressure stripping plays a significant role in quenching star formation in the nearest massive galaxy cluster.